Preparation method and application of In2O3 high-temperature thermoelectric material

By introducing the second phase of InGaZnO4 in In2O3, using ball milling and discharge plasma sintering technology, the problem of low ZT value of In2O3 thermoelectric superiority is solved, and a significant improvement in the thermoelectric performance of In2O3 has been achieved.

CN119797416APending Publication Date: 2025-04-11ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510010098.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The thermoelectric superiority ZT value of In2O3 metal oxide is relatively low, mainly due to its high lattice thermal conductivity.

Method used

By introducing a trace amount of InGaZnO4 second phase into In2O3, ball milling method and discharge plasma sintering technology are used to reduce the lattice thermal conductivity of In2O3 and improve its electrical performance, thereby optimizing its thermoelectric performance.

Benefits of technology

The thermoelectric performance of In2O3 samples was significantly improved, and the room temperature thermal conductivity of IGZO samples was as low as 6W·m-1·K-1, and the ZT value at 600°C was increased to 0.15, which was more than twice that of pure In2O3.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797416A_ABST
    Figure CN119797416A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an In2O3 high-temperature thermoelectric material, In2O3 powder is used as a matrix, trace ZnO powder and Ga2O3 powder are doped, after high-energy ball milling and mixing, the In2O3 thermoelectric material with a trace InGaZnO4 second phase is prepared by adopting air calcination and discharge plasma sintering technology, In2O3, Ga2O3 and ZnO are mixed according to the molar ratio of In: Ga: Zn = 2-2x: x: x, and x is 0.02-0.12. The prepared In2O3 high-temperature thermoelectric material is applied to thermoelectric conversion products in a high-temperature environment. By introducing the second phase InGaZnO4, the electrical transport performance and the thermal transport performance of In2O3 can be cooperatively adjusted, and a very effective strategy is provided for improving the thermoelectric performance of In2O3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and relates to a preparation method and application of In2O3 high-temperature thermoelectric material. Background Art

[0002] As fossil fuels are about to be exhausted, sustainable energy has received widespread attention in recent years. As a green power generation technology, thermoelectric conversion technology can convert thermal energy into electrical energy and vice versa, and has the full potential to solve the growing energy consumption and environmental problems. Thermoelectric materials are the key components of thermoelectric conversion devices, and their thermoelectric conversion performance is evaluated by the quality factor ZT value, ZT = S 2 σT / κ. Where σ is the electrical conductivity, S is the Seebeck coefficient, T is the absolute temperature, and κ is the thermal conductivity. 2 σ is also called the power factor and is used to evaluate the electrical transport properties of a material. Therefore, high-performance thermoelectric materials should have both a high power factor and low thermal conductivity.

[0003] The n-type semiconductor In2O3 is considered to be a promising high-temperature thermoelectric material with good chemical and thermal stability. It can operate at temperatures up to 1400°C, such as in harsh working environments such as gas turbines, jets and rocket engines. On the other hand, indium oxide has high manufacturability and can be prepared by traditional sintering, inorganic salt decomposition, microemulsion, uniform precipitation and template methods. Therefore, indium oxide is very likely to become an excellent candidate material in the field of high-temperature thermoelectrics. Although indium oxide has very excellent electrical transport properties, the thermoelectric figure of merit of In2O3 is still relatively low compared with better performing thermoelectric materials such as SnSe and GeTe. One important factor is that In2O3 has a higher lattice thermal conductivity. Generally speaking, due to the strong atomic bonding force in metal oxides and the large phonon transmission speed, the thermal conductivity is significantly higher. Studies have reported that the thermal conductivity of In2O3 is as high as 13.2 W·m at room temperature. -1 ·K -1 , which makes its thermoelectric figure of merit ZT value significantly low, which is the main disadvantage of In2O3 metal oxide in thermoelectric conversion applications. Summary of the invention

[0004] In order to solve the technical problem that the thermoelectric figure of merit ZT value of In2O3 metal oxide is relatively low, the purpose of the present invention is to provide a method for preparing In2O3 high-temperature thermoelectric material, adopt multiple strategies such as grain nano-sizing and introduction of a second phase to reduce the thermal conductivity of the metal oxide, and at the same time improve its electrical properties by introducing a second phase to achieve optimization of its overall thermoelectric performance, thereby improving the thermoelectric figure of merit ZT value of the In2O3 material, and by adding a trace amount of InGaZnO4 second phase into In2O3, the lattice thermal conductivity of In2O3 is reduced and the power factor is improved to optimize the electrical transport performance, thereby significantly improving the thermoelectric performance of the In2O3 sample.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] A method for preparing In2O3 high-temperature thermoelectric material comprises the following steps: using In2O3 powder as a matrix, adding ZnO powder and Ga2O3 powder, ball milling and mixing, and then adopting air calcination and spark plasma sintering technology to jointly prepare In2O3 containing InGaZnO4 second phase, wherein In2O3, Ga2O3 and ZnO are mixed at a molar ratio of In:Ga:Zn of 2-2x:x:x, and x is 0.02-0.12.

[0007] Further steps include:

[0008] S1: Weigh In2O3 powder, ZnO powder and Ga2O3 powder according to proportion;

[0009] S2: ball-milling the powders weighed in step S1 to obtain a mixture powder of In2O3 powder, ZnO powder and Ga2O3 powder;

[0010] S3: drying the mixed powder in step S2, and then calcining it in air to obtain a calcined powder;

[0011] S4: The powder calcined in step S3 is sintered by spark plasma to obtain a dense block material, which is an In2O3 high-temperature thermoelectric material containing an InGaZnO4 second phase.

[0012] Furthermore, the ball milling in step S2 uses ethanol as solvent, and the mass ratio of anhydrous ethanol to the mixed powder is 5:1; the ball milling speed is 550 r·min -1 , time is 12h.

[0013] Furthermore, the air calcination in step S3 is carried out at a temperature of 1000° C. and for a time of 6 hours.

[0014] Furthermore, the reaction conditions of the spark plasma sintering in step S4 are vacuum conditions, a pressure of 50 MPa, and a heating rate of 100 ° C. min-1 The sintering temperature is 950℃, the sintering time is 5min, and after sintering, it is cooled naturally to obtain an In2O3 block with a diameter of 15mm and a height of 10mm containing a trace amount of InGaZnO4 second phase.

[0015] Furthermore, the present application also provides an application of In2O3 high-temperature thermoelectric material in the preparation of thermoelectric conversion products.

[0016] Through the above technical solution, the beneficial effects of the present invention are:

[0017] (1) This application selects n-type semiconductor In2O3 as the research object, and significantly improves the thermoelectric performance of In2O3 samples by reducing its lattice thermal conductivity by introducing a second phase and vacancy defects.

[0018] (2) An In2O3 composite material (IGZO) containing a second phase InGaZnO4 was synthesized by ball milling combined with spark plasma sintering (SPS). The room temperature conductivity of the IGZO sample is more than five times that of pure In2O3. In addition, positron annihilation testing showed that there were a large number of vacancy defects in the sample, and the presence of the second phase increased the phonon scattering at the grain boundaries. These scattering centers led to a significant reduction in the mean free path of phonons, making the thermal conductivity of In2O3 as low as 6 W·m at room temperature. -1 ·K -1 . Ultimately, the ZT value of the IGZO sample at 600°C increased to 0.15, which is more than twice the ZT value of pure In2O3; the main body of the material in this application is In2O3, and only a trace amount of InGaZnO4 is needed to improve the thermoelectric performance of the In2O3 main body. Among them, the introduction of InGaZnO4 realizes the synergistic optimization of the electrical transport performance and thermal transport performance of In2O3. Combining the advantages of InGaZnO4 and In2O3, only a small amount of InGaZnO4 is needed to ensure the stability of the In2O3 thermoelectric material and improve the thermoelectric performance of In2O3. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD pattern of the sample in this application;

[0020] Figure 2 is the relationship between the relative proportion of the second phase InGaZnO4 and the ZnO content;

[0021] Figure 3 FE-SEM images of the samples of the present application with different Ga and Zn contents;

[0022] Figure 4 (a) backscattered electron image (BSE) and (bd) element distribution maps of the corresponding areas of the sample IGZO-0.12 of this application;

[0023] Figure 5 The positron lifetime components τ1, τ2, intensity I2 and average lifetime τ of the samples of the present application with different Ga and Zn contents are av ;

[0024] Figure 6 The changes of (a) conductivity and (b) Seebeck coefficient of the samples of this application with the test temperature;

[0025] Figure 7 (a) Hall carrier concentration and mobility of the samples in this application and (b) S 2 Variation of σ with test temperature;

[0026] Figure 8 The changes of (a) total thermal conductivity and (b) lattice thermal conductivity of the samples of the present application with the test temperature;

[0027] Fig. 9 The ZT value of the sample in this application changes with the test temperature DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0029] The present application adopts a planetary high-energy ball mill to mix and refine the oxides, and the ball mill jar and grinding balls are both made of agate.

[0030] The SPS equipment used is the SPS-211Lx spark plasma sintering furnace produced by Fuji DENPA KOKI Co., Ltd.

[0031] Air calcination uses a high temperature tube furnace

[0032] The raw materials are gallium oxide, zinc oxide, and indium oxide powders, all purchased from Aladdin, with a purity of 99.99%

[0033] Comparative Example 1: In2O3 powder (IGZO-0)

[0034] The commercially available In2O3 powder was pressed into a dense block by spark plasma sintering, and then sintered at 950℃ for 5 min at a pressure of 50 MPa and a heating rate of 100℃·min -1 After sintering, the mixture was cooled naturally. The above steps were all carried out under vacuum. An In2O3 block with a diameter of 15 mm and a height of 10 mm was obtained, which did not contain InGaZnO4 and was recorded as IGZO-0.

[0035] Then, a wire cutting machine was used to cut In2O3 into rectangular blocks of 3mm×3mm×10mm for electrical performance testing, and the thermal conductivity test was carried out using blocks with a diameter of 12.5mm and a thickness of 1mm.

[0036] Comparative Example 2: Preparation of InGaZnO4 powder

[0037] S1: Weigh 3.538g In2O3 powder, 2.388g ZnO powder and 2.074g Ga2O3 powder according to the proportion;

[0038] S2: The In2O3 powder, ZnO powder and Ga2O3 powder weighed in step S1 are mixed by ball milling; wherein ethanol is used as the solvent for ball milling, the mass ratio of anhydrous ethanol to raw materials is 5:1, the ball milling time is 12h, and the ball mill speed is 550r·min -1 After the ball milling, a mixture of In2O3 powder, ZnO powder and Ga2O3 powder is obtained;

[0039] S3: drying the mixture powder obtained in step S2 at 80° C. for 12 h. After drying, calcining the mixture powder in a high-temperature tube furnace at 1000° C. for 6 h in an air atmosphere, and then cooling the furnace to obtain a calcined powder;

[0040] S4: Sintering by spark plasma The calcined powder obtained in step S3 is sintered in a spark plasma sintering furnace under vacuum conditions, a pressure of 50 MPa, and a heating rate of 100 °C min -1 The sintering temperature is 950℃, the sintering time is 5min, and after sintering, it is cooled naturally to obtain an In2O3 block with a diameter of 15mm and a height of 10mm containing a trace amount of InGaZnO4 second phase.

[0041] Then, a wire cutting machine was used to cut In2O3 into rectangular blocks of 3mm×3mm×10mm for electrical performance testing, and the thermal conductivity test was carried out using blocks with a diameter of 12.5mm and a thickness of 1mm.

[0042] Example 1: IGZO-0.02

[0043] A method for preparing In2O3 high-temperature thermoelectric material, specifically comprising the following steps:

[0044] S1: Weigh 7.900g In2O3 powder, 0.054g ZnO powder and 0.047g Ga2O3 powder in proportion;

[0045] S2: The In2O3 powder, ZnO powder and Ga2O3 powder weighed in step S1 are mixed by ball milling; wherein ethanol is used as the solvent for ball milling, the mass ratio of anhydrous ethanol to raw materials is 5:1, the ball milling time is 12h, and the ball mill speed is 550r·min -1 After the ball milling, a mixture of In2O3 powder, ZnO powder and Ga2O3 powder is obtained;

[0046] S3: drying the mixture powder obtained in step S2 at 80° C. for 12 h. After drying, calcining the mixture powder in a high-temperature tube furnace at 1000° C. for 6 h in an air atmosphere, and then cooling the furnace to obtain a calcined powder;

[0047] S4: Sintering by spark plasma The calcined powder obtained in step S3 is sintered in a spark plasma sintering furnace under vacuum conditions, a pressure of 50 MPa, and a heating rate of 100 °C min -1 The sintering temperature is 950℃, the sintering time is 5min, and after sintering, it is cooled naturally to obtain an In2O3 block with a diameter of 15mm and a height of 10mm containing a trace amount of InGaZnO4 second phase, which is recorded as IGZO-0.02.

[0048] Then, a wire cutting machine was used to cut In2O3 into rectangular blocks of 3mm×3mm×10mm for electrical performance testing, and the thermal conductivity test was carried out using blocks with a diameter of 12.5mm and a thickness of 1mm.

[0049] Example 2: IGZO-0.04

[0050] The difference from Example 1 is: S1: 7.795 g In2O3 powder, 0.110 g ZnO powder and 0.095 g Ga2O3 powder are weighed in proportion; the product is recorded as: IGZO-0.04.

[0051] Example 3: IGZO-0.06

[0052] The difference from Example 1 is: S1: 7.690g In2O3 powder, 0.166g ZnO powder and 0.144g Ga2O3 powder are weighed in proportion; the product is recorded as: IGZO-0.06.

[0053] Example 4: IGZO-0.08

[0054] The difference from Example 1 is: S1: 7.584g In2O3 powder, 0.223g ZnO powder and 0.193g Ga2O3 powder are weighed in proportion; the product is recorded as: IGZO-0.08.

[0055] Example 5: IGZO-0.12

[0056] The difference from Example 1 is: S1: 7.366g In2O3 powder, 0.339g ZnO powder and 0.294g Ga2O3 powder are weighed in proportion; the product is recorded as: IGZO-0.12.

[0057] In summary, according to Examples 1-5 and Comparative Examples 1-2, the following conclusions were obtained through experimental characterization.

[0058] Depend on Figure 1 , analysis shows that the diffraction peaks of all samples match the diffraction peaks in the standard card of In2O3 cubic ferromanganese structure (JCPDS card number: 06-0416), and the space group is In addition, all samples show good crystallinity and sharp diffraction peaks. For the IGZO-0.08 sample, an obvious diffraction peak of the second phase InGaZnO4 can be observed, and the intensity of the diffraction peak gradually increases with the increase of Zn and Ga contents.

[0059] Depend on Figure 2 It can be seen that the relative ratio of the characteristic peak of InGaZnO4 and the total peak of XRD is proportional to the ZnO content, which means that with the increase of the content of Zn and Ga elements introduced, the content of InGaZnO4 in the synthesized sample also increases. For samples with low Zn and Ga contents, they also contain InGaZnO4, but their characteristic diffraction peaks are not obvious. In addition, it should be noted that the diffraction peak positions of different samples do not move significantly with the increase of Ga and Zn contents. It can be considered that when Zn and Ga elements are added to In2O3, InGaZnO4 will be formed first, rather than incorporating Zn and Ga elements into the lattice of In2O3.

[0060] Depend on Figure 3 From the analysis, it can be seen that the average grain size obtained by XRD is 20-30 nm, which indicates that the particles observed by FESEM are formed by grain aggregation. In addition, as shown in Table 1, the density of the sample decreases with the increase of Zn and Ga contents.

[0061] Table 1 Grain size and density of different IGZO samples

[0062]

[0063] Depend on Figure 4 Analysis shows that Figure 4 (a) shows the backscattered electron (BSE) image of IGZO-0.12, where the dark gray area is the micrometer-sized second phase InGaZnO4, which is uniformly distributed in the sample, and the black dot-like morphology is the hole in the sample. Figure 4(bd) are the element distribution diagrams corresponding to the BSE image area. The In element is significantly reduced in the second phase area, while the signals of Ga and Zn elements are significantly enhanced in the second phase area, which further proves the existence of the InGaZnO4 second phase, which is consistent with the results of XRD analysis.

[0064] Depend on Figure 5 Analysis shows that with the increase of Zn and Ga content, τ1 shows an upward trend from 161ps to 176ps, indicating that the vacancy size is gradually increasing. For τ2, it is related to the change in the size of vacancy clusters. Except for pure In2O3, τ2 of other samples has the same upward trend as τ1, showing that the size of vacancy clusters also increases with the increase of Zn and Ga content. The τ2 of IGZO-0.12 is as high as 325ps. In addition, I2 is the relative concentration of vacancy clusters corresponding to τ2. The I2 of pure In2O3 is as high as 59%, which means that the concentration of vacancy clusters in pure In2O3 is significantly higher than that of other samples. In addition, with the increase of Zn and Ga content, the relative concentration of vacancy clusters decreases instead, indicating that the introduction of Zn and Ga is not conducive to the generation of vacancy clusters. It should be noted that the average lifetime τ av (=τ1I1+τ2I2) can reflect the overall vacancy information inside the sample and is not affected by the lifetime spectrum resolution function. av As high as 256ps, which is much higher than the bulk lifetime of perfect In2O3 (183ps), indicating that the pure In2O3 sample contains a large number of vacancy defects compared with other samples. av It is stable at around 195ps, which is also higher than the bulk lifetime of In2O3 (183ps), confirming that there are still a certain number of small vacancies inside these samples.

[0065] Figure 6 Analysis shows that the conductivity (σ) of all IGZO samples decreases significantly with the increase of test temperature, which is a typical metallic behavior. With the increase of Zn and Ga content, σ at room temperature basically shows an upward trend. The conductivity of IGZO-0.12 at room temperature reaches 3.39×10 4 S·m -1 , which is 5 times higher than the conductivity of pure In2O3. In the prior art, when InGaZnO4 is not doped with impurity elements, its carrier concentration (n) is still as high as ~10 20 cm -3 , it is a very good conductive crystal. Figure 1 and Figure 2The results show that the content of InGaZnO4 gradually increases with the introduction of Zn and Ga. Therefore, the increase in the conductivity of IGZO-0.12 is likely related to the increase in the content of InGaZnO4. In order to explore the relationship between the increase in sample conductivity and InGaZnO4, we used the same experimental preparation method and conditions to synthesize InGaZnO4 and tested its conductivity. Figure 6 (a) It can be seen that the conductivity of InGaZnO4 at room temperature is as high as 8.86×10 4 S·m -1 , which is more than 10 times the conductivity of pure In2O3. Therefore, it can be proved that the improvement of the conductivity of the IGZO series samples is due to the increase in the InGaZnO4 content. Figure 6 (b) shows the variation of Seebeck coefficient of IGZO samples with temperature (room temperature to 600°C). With the increase of Zn and Ga content, |S| decreases regularly. According to the single parabolic band model:

[0066]

[0067] From formula (1), we can get the Seebeck coefficient and n 2 / 3 For IGZO samples, it can be found that the change trend of |S| of different samples at room temperature is basically opposite to the change of carrier concentration at room temperature. The Seebeck coefficient of pure In2O3 is as high as 145.11μ·V·K at room temperature. -1 According to the measured conductivity and Seebeck coefficient, the power factor (PF = S 2 σ).

[0068] Figure 7 The analysis shows that the carrier concentration of IGZO-0.12 is as high as 4.19×10 19 cm -3 , which is nearly 15 times higher than the carrier concentration of pure In2O3. Of course, the introduction of InGaZnO4 will inevitably enhance the scattering of electrons, causing the carrier mobility of IGZO-0.12 to drop to 43.72cm 2 ·V -1 ·s -1 However, the conductivity of IGZO-0.12 is still as high as 3.39×10 4 S·m -1 This is because the significant increase in carrier concentration offsets the effect of decreased carrier mobility on conductivity. At 600°C, the PF of IGZO-0.04 is 0.47 mW·m -1 ·K -2 , which is more than twice that of pure In2O3. This can be attributed to the optimization of the electrical transport properties of In2O3 by the second phase InGaZnO4.

[0069] Figure 8 (a) shows the total thermal conductivity (κ tot ) changes from room temperature to 600 °C. For all samples, κ tot Both decrease monotonically with temperature, which can be attributed to the Umklapp phonon-phonon scattering mechanism. With the increase of Ga and Zn content, the κ tot For the IGZO-0.12 sample, its κ tot 6.05 W·m at room temperature -1 ·K -1 , as low as 2.57W·m at 600℃ -1 ·K -1 In order to explore the mechanism of the change in thermal conductivity of IGZO samples, the formula κ = κ E +κ L and κ E = L·σ·T to obtain the trend of lattice thermal conductivity changing with temperature, such as Figure 8 (b) It is worth noting that the lattice thermal conductivity shows a consistent trend with the total thermal conductivity, indicating that the total thermal conductivity of IGZO is mainly affected by the lattice thermal conductivity. For samples containing InGaZnO4, the lattice thermal conductivity at room temperature decreases monotonically with the increase of Zn and Ga. Figure 8 The lattice thermal conductivity of the IGZO sample in (b) is significantly reduced, which can be attributed to vacancy defect scattering, grain boundary scattering and second phase scattering mechanisms. For IGZO samples containing Zn and Ga, the lattice thermal conductivity at room temperature decreases monotonically with the increase of Zn and Ga content. InGaZnO4 as a second phase will inevitably increase the number of grain boundaries, so the number of phonons scattered by grain boundaries will increase. In addition, the average grain size of all samples obtained by XRD is 20-30nm. Nanoscale grains further increase the number of grain boundaries that can scatter phonons. Therefore, the κ of IGZO-0.12 L The lowest value is 2.02 W·m at 600℃. -1 ·K -1 , which is lower than other reports. It is worth noting that the κ of pure In2O3 without a secondary phase is tot It is lower than IGZO-0.02 and even lower than IGZO-0.06. According to the results of positron annihilation test, the size and relative concentration of vacancy clusters of pure In2O3 are higher than those of other samples. These vacancy clusters can effectively scatter phonons with a mean free path comparable to their size, so the lattice thermal conductivity of pure In2O3 is significantly reduced.

[0070] Fig. 9Analysis shows that in this work, the ZT value of the IGZO-0.08 sample at 600°C is 0.15, which is more than twice the ZT value of pure In2O3.

[0071] In summary, in this research, IGZO samples with different Zn and Ga contents were prepared by solid phase method and spark plasma sintering technology, and the effect of the introduction of the second phase InGaZnO4 on the thermoelectric properties of In2O3 was studied. Both phase structure analysis and microstructure characterization proved the existence of InGaZnO4. Due to the excellent conductivity of InGaZnO4, the conductivity of IGZO-0.12 was optimized to 3.39×10 4 S·m -1 The power factor of IGZO-0.04 is as high as 0.47mW·m -1 ·K -2 In addition, due to the strong scattering effect of grain boundaries, vacancy defects and second-phase phonons, the thermal conductivity of IGZO-0.12 drops to 2.57 W·m at 600°C. -1 ·K -1 Finally, the ZT value of IGZO-0.08 is 0.15 at 600°C, which is more than twice that of pure In2O3, and will reach higher values ​​as the test temperature increases. Therefore, the introduction of Zn and Ga to prepare In2O3 composites containing the second phase InGaZnO4 is a promising strategy to improve the thermoelectric properties of In2O3.

[0072] The embodiments described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made on the principles of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A method for preparing In2O3 high-temperature thermoelectric material, characterized in that: The following steps are involved: In2O3 powder is used as the matrix, ZnO powder and Ga2O3 powder are added, and after ball milling, In2O3 containing InGaZnO4 is prepared by air calcination and spark plasma sintering technology, wherein In2O3, Ga2O3 and ZnO are mixed in a molar ratio of In:Ga:Zn of 2-2. x : x : x Mixing x It is 0.02-0.

12.

2. The method for preparing an In2O3 high-temperature thermoelectric material according to claim 1, characterized in that: The following steps are involved: S1: Weigh In2O3 powder, ZnO powder and Ga2O3 powder according to proportion; S2: ball-milling the powders weighed in step S1 to obtain a mixture powder of In2O3 powder, ZnO powder and Ga2O3 powder; S3: drying the mixed powder in step S2, and then calcining it in air to obtain a calcined powder; S4: The powder calcined in step 3 is sintered by discharge plasma to obtain a dense block material, which is an In2O3 high-temperature thermoelectric material containing InGaZnO4.

3. The method for preparing an In2O3 high-temperature thermoelectric material according to claim 2, characterized in that: The ball milling in step S2 uses anhydrous ethanol as solvent, and the mass ratio of anhydrous ethanol to the mixed powder is 5:1; the ball milling speed is 550 r·min -1 , time is 12 h.

4. The method for preparing an In2O3 high temperature thermoelectric material according to claim 2, characterized in that: The air calcination temperature in step S3 is 1000°C and the time is 6 h.

5. The method for preparing an In2O3 high temperature thermoelectric material according to claim 2, characterized in that: The reaction conditions of the spark plasma sintering in step S4 are vacuum, pressure of 50 MPa, and heating rate of 100 °C·min -1 The sintering temperature is 950 ℃ and the sintering time is 5 min. After the sintering is completed, it is cooled naturally to obtain an In2O3 block containing the InGaZnO4 second phase.

6. Use of the In2O3 high-temperature thermoelectric material according to claim 1 in the preparation of thermoelectric conversion products.